PKM OPTIMALISASI URINE KELINCI MENJADI PUPUK ORGANIK CAIR (POC) TANAMAN SELEDRI PADA KELOMPOK TANI MUARA SIBAN KOTA PAGAR ALAM - Ferry Putrawansyah; Asep Syaputra; Vike Itteridi (LPPM Universitas Bina Bangsa, 2023)
The Tunas Baru Farmers Group in Muara Siban Village is one of the farmer groups that has a large area of land to produce good vegetables in the city of Pagar Alam, but the wider the agricultural cultivation area, the higher the need for fertilizer and pesticides, coupled with the high price of fertilizer. causing agricultural yields to decline. Apart from having agricultural land, this farming group also has quite a lot of rabbit livestock, but rabbit urine which is rich in nitrogen has not been used as an alternative fertilizer for agricultural land. Rabbit urine liquid organic fertilizer (POC) is urine waste from rabbit farms that contains nutrients that are good for plants and can be used as an alternative treatment. The treatments used are several concentrations of rabbit urine, and a combination of urine with inorganic fertilizer. Rabbit urine is fermented before use by mixing EM4/Yakult as a probiotic, brown sugar/granulated sugar and 5 liters of rabbit urine. The experimental results showed that there was an effect of using fermented rabbit urine on leaf area, root volume and dry weight of cocoa seedlings at the age of 16 WAP. P The conclusion in this service is that by reducing the use of inorganic fertilizers to <50% and adding Rabbit Urine POC, it can have an influence on celery plants so that at the age of 2, 3 and 4 WAP, the difference in rabbit urine concentration treatment has a statistically significant effect. on the number of celery leaves. Furthermore, entering the plant age of 5 WAP, it was seen that the differences in treatment given had a statistically insignificant effect on the variable number of leaves. And this Rabbit Urine POC has proven successful in making celery plants grow well and develop well so that they can be marketed/used by other farmers